Trajectory planning and optimization for UAV communication: A review. (17th February 2020) - Indu,; Singh, Rishipal
Abstract: With the huge advantages and increasing growth of unmanned aerial vehicles (UAVs), their popularity expanded and used in every aspect of our lives including government, industry, environment and society. In this paper, a review on UAV communication has been presented that throws light on trajectory planning, its optimization and various issues in a summarized way. The parameters selected for review are communication type, trajectory and techniques used.Technical challenges are explored and some fundamental trade-offs among throughput, energy and delay are observed. Some findings and future directions for UAV communication are presented.